(untitled) (Intent Research Scientific Journal, 2023)
The problem of using gaming technologies for teaching schoolchildren to solve physical problems is discussed. The possibilities of a virtual environment for organizing gaming learning activities are considered. The analysis of the domestic and foreign gaming resources in physics presented in the open access is given. The necessity of replenishing the modern resource base of this type, including the section of computer games for training sessions on solving physical problems, is substantiated. The didactic game "Golf" developed by the authors of the article is presented. The game model of the resource is implemented in the 3D simulation mode in the Unity environment. The content of training tasks, dynamic game video sequence, the interactive nature of the interaction of participants with game objects and the competitive effect of the game are aimed at consolidating and developing the knowledge, skills and abilities previously acquired by the student in solving physical problems on the topic "Kinematics".